A case of reticulate acropigmentation of Kitamura: Dowling Degos disease overlap with unusual clinical manifestations - Biju Vasudevan; Rajesh Verma; Sonia Badwal; Vijendran Pragasam; Nikhil Moorchung; Ambresh Badad (Wolters Kluwer Medknow Publications, 2014)
Reticulate hyperpigmentary disorders are a group of rare genetic pigmentary abnormalities which includes reticulate acropigmentation of Kitamura (RAPK), Dowling-Degos disease (DD), reticulate acropigmentation of Dohi (RAPD), Haber's syndrome, and Galli-Galli disease. A 25-year-old male presented with asymptomatic dark-colored lesions on his hands and feet with light-colored skin lesions involving the trunk since three years. Dermatological examination revealed hyperpigmented macules in a reticulate pattern involving the dorsa of the hands and feet, front and sides of the neck, axillae, periorbital region, and groin. Multiple pits were present over both palms, with breaks in dermatoglyphics. He also had multiple nonacne facial scars predominantly on the nose and malar areas. The patient had overlapping features of RAPK and DDD. In addition, he also had hypopigmented macules and acneiform facial scars. Such an overlap of features of reticulate pigmentation has not been previously reported in the literature.